2016
DOI: 10.1371/journal.pone.0164562
|View full text |Cite
|
Sign up to set email alerts
|

Paedomorphosis as an Evolutionary Driving Force: Insights from Deep-Sea Brittle Stars

Abstract: Heterochronic development has been proposed to have played an important role in the evolution of echinoderms. In the class Ophiuroidea, paedomorphosis (retention of juvenile characters into adulthood) has been documented in the families Ophiuridae and Ophiolepididae but not been investigated on a broader taxonomic scale. Historical errors, confusing juvenile stages with paedomorphic species, show the difficulties in correctly identifying the effects of heterochrony on development and evolution. This study pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 46 publications
(67 reference statements)
5
33
0
Order By: Relevance
“…The morphological criterion well agrees with recent molecular data in which the Corambidae never appear as basal-most dorids but are placed inside of the group of families which possess exactly the same type of specialized buccal apparatus [36,38]. A parallel case is represented by ophiuroid echinoderms, where previously some strongly simplified groups were considered ancestral ones [39], however it was shown that such groups have specific features that are highly similar to the postlarval stages of common ophiuroid families with complex adult stages [40,41], thus fulfilling the first criterion of paedomorphosis. Most recently, a genome-scale analysis of a whole class of Ophiuroidea confirmed that previously assessed"ancestrally simple" ophiuroid taxa are nested within ophiuroid families with complex adult morphology [42].…”
Section: Criteria For Distinguishing the Paedomorphic State In Metazoanssupporting
confidence: 87%
See 3 more Smart Citations
“…The morphological criterion well agrees with recent molecular data in which the Corambidae never appear as basal-most dorids but are placed inside of the group of families which possess exactly the same type of specialized buccal apparatus [36,38]. A parallel case is represented by ophiuroid echinoderms, where previously some strongly simplified groups were considered ancestral ones [39], however it was shown that such groups have specific features that are highly similar to the postlarval stages of common ophiuroid families with complex adult stages [40,41], thus fulfilling the first criterion of paedomorphosis. Most recently, a genome-scale analysis of a whole class of Ophiuroidea confirmed that previously assessed"ancestrally simple" ophiuroid taxa are nested within ophiuroid families with complex adult morphology [42].…”
Section: Criteria For Distinguishing the Paedomorphic State In Metazoanssupporting
confidence: 87%
“…This additional criterion should be applied especially carefully, because it is indirect, compared to the two main criteria. For example, it is well established that deep-sea environments facilitate the appearance of paedomorphic organisms, including such different groups as fishes [43] and ophiuroids [40,41]. An environment may contain non-paedomorphic groups as well, so such ecological information cannot be used solely as an indicative criterion and must be checked against the two main ones.…”
Section: Criteria For Distinguishing the Paedomorphic State In Metazoansmentioning
confidence: 99%
See 2 more Smart Citations
“…Essentially new results were obtained for the classification of the Nudibranchia (Mollusca) order, in which three new families were described [11]. The importance of pedomorphosis in the formation of new taxa of high rank and the need to study the diversity of ontogenetic patterns for their identification has been demonstrated within the framework of the ontogenetic systematics concept [12][13][14][15]. The molecular phylogenetic analysis demonstrated the monophily of eight genera of the Acrothoracica (Copepoda) superorder [16].…”
Section: Animalsmentioning
confidence: 99%